Salvinia weevil, Cyrtobagous salviniae (Calder & Sands) (Insecta: Coleoptera: Curculionidae) - Patricia Prade; Eutychus Kariuki; Adam Dale (EDIS, 2019)
The salvinia weevil, Cyrtobagous salviniae (Calder & Sands) (Coleoptera: Curculionidae) (Figure 1), is a subaquatic (underwater) herbivorous insect native to Brazil (Calder and Sands 1985). This insect feeds on the invasive aquatic plants Salvinia molesta D. S. Mitchell and Salvinia minima (Baker). This insect is an effective classical biological control agent used in several countries to control the invasive giant salvinia, Salvinia molesta (D. S. Mitch). Feeding by Cyrtobagous salviniae larvae and adults kills its invasive host plants and restores recreational, agricultural, and ecosystem functions in aquatic systems. In the United states, the insect has been credited for controlling Salvinia minima in Florida (Jacono et al. 2001) and causing the decline of Salvinia molesta in Texas and Louisiana (Tipping et al. 2008).